KNOWLEDGE LEVEL OF AGRICULTURAL EMPLOYEES IN DUHOK DIRECTORATE ON INTEGRATED PEST MANAGEMENT - Hashim Murad (Mesopotamia Journal of Agriculture)
The research aimed to identify the knowledge levels of the Duhok Agriculture employees on integrated Pest Management (IPM) fields. The correlation between the degree of employee knowledge and some independent variables identified. And to identify some personal and functional characteristics of the researchers consisted of two parts. The first part which contained the independent variables of the respondents and the second part included a test the level of knowledge of agricultural employees in the field of IPM including 38 items distributed over the 6 parts: 1. General principles 2. Control by agricultural methods 3. Physical control 4. Biological control. 5. Legislative control 6. Chemical control. Data were collected through a personal interview with simple random samples of agricultural employees, representing 25% of the total of 52 respondents. The results showed that the degree of knowledge of Duhok agriculture employees in the field of integrated management in general was moderate and tends to high. Moreover, employees’ knowledge in the field of biological control and their lack of experience with regard to biological enemies, predators and parasites was low. On the other hand, there were a significant correlation between the degree of knowledge of the respondents and each of the independent variables, (the number of family members, specialization, education level, and previous training). On the other hand, there was no correlation with other variables (Age, gender, work location, upbringing, number years of agricultural service, years of preventive agricultural service, Job title, and Information sources in the field of integrated pest management). The researcher recommended that the necessity of paying attention to the topic of IPM through expanding the scope of seminars and extension to increase the knowledge and information of agricultural employees, and work to prepare and implement the intensive and specialized training programs carried by the Ministry of Agriculture in the region.